Evaluation of Antibacterial Activity of Cymbopogon Nardus L. on The Growth of Enterococcus Faecalis - Rosada Sintya Dwi; Diah Tanjung; Shanty Chairani; Rini Bikarindrasari; Siti Rusdiana Puspa Dewi (Denta Journal Kedokteran Gigi, 2021)
Background: Cymbopogon nardus L. known as citronella grass is traditional medicinal plant that contains saponins, polyphenols, alkaloids, flavonoids, and essential oil. Based on the previous study, it is known that it has antibacterial properties. Objective: The aim of this study was to determine antibacterial activity of Cymbopogon nardus L. in inhibiting the growth of Enterococcus faecalis. Methods: The samples were Cymbopogon nardus L. extracts with concentration of 1%, 3%, 5%,7%, 9%, and 5% NaOCl as positive control. Antibacterial activity of citronella extract against E. faecalis was observed with the formation of inhibitory zone diameter in agar. Data were analyzed using SPSS with one-way ANOVA and LSD test. Result: The result showed that Cymbopogon nardus L. was able to inhibit the growth of E. faecalis at concentration 1%,3%,5%,7% and 9%. There was a significant difference in antibacterial activity among all groups. It showed that concentration of 9% showed the highest zone of inhibition, but it was not as effective as NaOCl 5%. NaOCl showed the highest zone of inhibition. Conclusion: Cymbopogon nardus L. had antibacterial activity in inhibiting the growth of E. faecalis. The higher the concentration of citronella extract, the higher the antibacterial activity possessed.